Oral health technicians in Brazilian primary health care: potentials and constraints - Dulce Maria Lucena de Aguiar; Nilce Emy Tomita; Maria de Fátima Antero Sousa Machado; Cleide Lavieri Martins; Paulo Frazão (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
Different perspectives on the role of mid-level workers in health care might represent a constraint to health policies. This study aimed to investigate how different agents view the participation of oral health technicians in direct activities of oral healthcare with the goal of understanding the related symbolic dispositions. Theoretical assumptions related to inter-professional collaboration and conflicts in the field of healthcare were used for this analysis. A researcher conducted 24 in-depth interviews with general dental practitioners, oral health technicians and local managers. The concepts of Pierre Bourdieu supported the data interpretation. The results indicated inter-professional relations marked by collaboration and conflict that reflect an action space related to different perspectives of primary care delivery. They also unveiled the symbolic devices related to the participation of oral health technicians that represent a constraint to the implementation of oral health policy, thus reducing the potential of primary health care in Brazil.